Sosialisasi dan Implementasi Aplikasi SPP pada Pondok Pesantren Walisongo Pontianak - Linawati, Safitri; Latif, Abdul; Anna, Anna; Murni, Sri (Society : Jurnal Pengabdian Masyarakat, 2024)
Management of Education Development Contributions (SPP) at the Walisongo Pontianak Islamic Boarding School plays an important role in maintaining the continuity of education, but is often faced with administrative challenges in recording, monitoring and reporting finances accurately and on time. In the era of digitalization, the use of technology is considered an effective solution in overcoming these obstacles. Through this community service, it offers several solutions to deal with the problems that occur, one of which is the SPP application grant at the Walisongo Pontianak Islamic Boarding School. Development of the SPP Application as an innovative step to increase administrative efficiency. Based on the analysis, the technology application approach is expected to help the Walisongo Pontianak Islamic Boarding School improve the SPP administration system, simplify the recording process, financial reporting, and speed up the transparency of SPP payments. The next step is to socialize and implement this application in Islamic boarding schools, with the hope that it can have a positive impact on managers, students and other stakeholders. The main goal is to make the Walisongo Pontianak Islamic Boarding School an example for similar institutions in facing administrative challenges in this era of digitalization. Thus, this service contributes to the development of technology for education and the management of Islamic educational institutions more effectively